2014
DOI: 10.1002/cctc.201402533
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐Transfer Catalysis in Oxidations Based on the Covalent Bonding of Hydrogen Peroxide to Amphiphilic Flavinium Salts

Abstract: The amphiphilic flavin derivatives 1,10‐ethylene‐bridged 3‐alkylalloxazinium salts (alkyl=butyl, octyl, dodecyl and hexadecyl) were shown to catalyse the chemoselective oxidation of sulfides to sulfoxides with hydrogen peroxide in chloroform/water or dichloromethane/water systems. The efficiency of the catalytic oxidation depended substantially on the pH of the aqueous phase to reach maximum values at pH 7. Under such conditions, the complete conversion of aliphatic and aromatic sulfides occurred within a maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…Covalent bonding to the alloxazine moiety has two positive effects on the behaviour of hydrogen peroxide in two‐phase oxidations: it causes peroxide to become sufficiently lipophilic to enter the organic medium containing the lipophilic substrate, and it substantially activates the peroxide for oxidation. The efficiency of catalytic oxidation substantially depended on the pH of the aqueous phase, reaching maximum values at pH 7, which is close to the p K R+ value of alloxazinium catalysts 3 (p K R+ = 7.2 for 3l ) 25…”
Section: Flavin Systems For Chemoselective Oxygenationssupporting
confidence: 59%
See 2 more Smart Citations
“…Covalent bonding to the alloxazine moiety has two positive effects on the behaviour of hydrogen peroxide in two‐phase oxidations: it causes peroxide to become sufficiently lipophilic to enter the organic medium containing the lipophilic substrate, and it substantially activates the peroxide for oxidation. The efficiency of catalytic oxidation substantially depended on the pH of the aqueous phase, reaching maximum values at pH 7, which is close to the p K R+ value of alloxazinium catalysts 3 (p K R+ = 7.2 for 3l ) 25…”
Section: Flavin Systems For Chemoselective Oxygenationssupporting
confidence: 59%
“…Very recently, we showed that the amphiphilic alloxazine derivatives 3g – k (Scheme ) act as phase‐transfer catalysts for chemoselective oxidation of sulfides to sulfoxides with hydrogen peroxide in chloroform/water or dichloromethane/water systems, with the aqueous phase consisting of buffered diluted hydrogen peroxide solution 25. In the absence of catalyst, only traces of product (sulfoxide) were detected, due to the low organic phase solubility of hydrogen peroxide, which cannot access sulfide in the organic phase; in contrast, complete conversion of aliphatic and aromatic sulfides occurred within a maximum of 24 h in the presence of 3h .…”
Section: Flavin Systems For Chemoselective Oxygenationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other relatively rare approaches based on covalent bonding of hydroperoxide species to fluorinated ketones2a,18 or on hydrogen bonding of H 2 O 2 to lipophilic phosphoric acid derivatives, have also been reported 19. Recently, we introduced the new concept of two‐phase H 2 O 2 oxidation utilizing the reversible covalent bonding of a hydroperoxide moiety to an amphiphilic flavinium salt 1 20. The lipophilic (non‐charged) flavin hydroperoxide 1‐OOH formed at the water‐chloroform interface is extracted into the organic phase where it can oxidize a lipophilic sulfide to the corresponding sulfoxide (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we report our idea to improve upon our concept of two‐phase oxidations using hydrogen peroxide, originally based on lipophilization and activation of hydroperoxide species by its covalent bonding to flavinium salts20 (Scheme ), by employing lipophilic pyridinium and diazinium catalysts (see structures 2 – 6 in Scheme ) whose 1‐methyl homologues were shown to be superior in the catalysis of H 2 O 2 ‐sulfoxidation in homogeneous media thanks to their simple synthesis and high stability compared to flavinium salts 15b. We expected that the combination of our two recent concepts – reported to simplify mild H 2 O 2 sulfoxidations – would result in an even simpler oxidation method for preparative organic chemistry.…”
Section: Introductionmentioning
confidence: 99%